Anti-Inflammatory Effects of Levalbuterol-Induced 11β-Hydroxysteroid Dehydrogenase Type 1 Activity in Airway Epithelial Cells - Randall, Matthew J.; Kostin, Shannon F.; Burgess, Edward J.; Hoyt, Laura R.; Ather, Jennifer L.; Lundblad, Lennart K.; Poynter, Matthew E. (Frontiers in Endocrinology, 2015)
Airway epithelial NF-kB activation is observed in asthmatic subjects and is a cause of airway inflammation in mouse models of allergic asthma. Combination therapy with inhaled short-acting b2-agonists and corticosteroids significantly improves lung function and reduces inflammation in asthmatic subjects. Corticosteroids operate through a number of mechanisms to potently inhibit NF-kB activity. Since b-agonists can induce expression of 11b-HSD1, which converts inactive 11-keto corticosteroids into active 11-hydroxy corticosteroids, thereby potentiating the effects of endogenous glucocorticoids, we examined whether this mechanism is involved in the inhibition of NF-kB activation induced by the b-agonist albuterol in airway epithelial cells. Treatment of transformed murine Club cells (MTCC) with (R)-albuterol (levalbuterol), but not with (S)- or a mixture of (R+S)- (racemic) albuterol, augmented mRNA expression of 11b-HSD1. MTCC were stably transfected with luciferase (luc) reporter constructs under transcriptional regulation by NF-kB (NF-kB/luc) or glucocorticoid response element (GRE/luc) consensus motifs. Stimulation of NF-kB/luc MTCC with lipopolysaccharide (LPS) or tumor necrosis factor-α (TNFα) induced luciferase activity, which was inhibited by pretreatment with (R)-, but not (S)- or racemic albuterol. Furthermore, pretreatment of GRE/luc MTCC with (R)-albuterol augmented 11-keto corticosteroid (cortisone) induced luciferase activity, which was diminished by the 11β-HSD inhibitor glycyrrhetinic acid (18β-GA). LPS- and TNFα-induced NF-kB/luc activity was diminished in MTCC cells treated with a combination of cortisone and (R)-albuterol, an effect that was inhibited by 18β-GA. Finally, pretreatment of MTCC cells with the combination of cortisone and (R)-albuterol diminished LPS- and TNFα-induced pro-inflammatory cytokine production. These results demonstrate that levalbuterol augments conversion of inactive 11-keto corticosteroids into the active 11-hydroxy form.